The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/mcg.0b013e318299c8dd
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Relative Diagnostic Yield of Esophagogastroduodenoscopy in Children With Gastroparesis

Abstract: Background Esophagogastroduodenoscopy (EGD) and gastric emptying scintigraphy (GES) are commonly performed in the evaluation of children with upper gastrointestinal (GI) symptoms. It has been presumed, but not clarified, that gastroparesis increases the likelihood of identifying abnormalities on EGD. We sought to determine whether the presence of gastroparesis influenced the diagnostic yield of EGD in children. Methods We conducted a retrospective chart review of children who underwent both an EGD and gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…The data showed that patients evaluated for gastroparesis (those with dyspeptic symptoms such as nausea, vomiting, bloating, and abdominal pain) have a high rate of findings on endoscopy, regardless of gastric emptying. The difference between the 2 groups was not statistically significant, a finding in contrast to recently published work by Wong et al (8), who suggested that the yield of endoscopy was actually greater in children with normal gastric emptying than in those with gastroparesis. There was no discernible effect of the order of testing on rates of diagnosis of gastroparesis or rates of positive findings on endoscopy in this population.…”
Section: Discussioncontrasting
confidence: 95%
“…The data showed that patients evaluated for gastroparesis (those with dyspeptic symptoms such as nausea, vomiting, bloating, and abdominal pain) have a high rate of findings on endoscopy, regardless of gastric emptying. The difference between the 2 groups was not statistically significant, a finding in contrast to recently published work by Wong et al (8), who suggested that the yield of endoscopy was actually greater in children with normal gastric emptying than in those with gastroparesis. There was no discernible effect of the order of testing on rates of diagnosis of gastroparesis or rates of positive findings on endoscopy in this population.…”
Section: Discussioncontrasting
confidence: 95%
“…An upper endoscopy may be performed to evaluate for gastric outlet obstruction and mucosal disease. Although a significant portion may have abnormal endoscopic findings, two pediatric studies found low yield of endoscopy in children with gastroparesis compared to non‐gastroparetic controls . Yet, practice guidelines by the American Society for Gastrointestinal Endoscopy suggest endoscopic evaluation to exclude a structural abnormality in children suspected to have gastroparesis who do not have a clear diagnosis after imaging studies …”
Section: Resultsmentioning
confidence: 99%
“…Although a significant portion may have abnormal endoscopic findings, two pediatric studies found low yield of endoscopy in children with gastroparesis compared to non-gastroparetic controls. 114,115…”
Section: Table 3 Outlines Relevant Pediatric Studies Of Various Diagn...mentioning
confidence: 99%
“…These two studies argue for endoscopy in these patients given the relatively high prevalence of positive histological findings. In contrast, Wong et al found that children with GP had fewer abnormal histological findings (27%, 19/70) when compared to children with normal gastric emptying (42%, 23/55), with gastritis and esophagitis also being the most common findings in the latter group. Whether the abnormal findings in children with GP contribute to the delay in gastric emptying is unclear.…”
Section: Diagnostic Evaluationmentioning
confidence: 88%